Perceived service quality and perceived value towards tourist satisfaction in beach tourism - H, Rheza Rahman; Sutisna, Deden; Razak, Anis Abd (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to examine the relationship between perceived quality and perceived value towards tourist satisfaction in beach tourism. Tourism industry especially in Bali contributes to a high percentage to economy with more than 40% tourist arrival. Understanding the needs and tourist expectations is important in order to serve them better. Data were collected from a questionnaire distributed to tourist at selected top five beach tourism. 200 respondents gathered and data were analyzed using structural equation modelling. The results indicate that both predictors are equally important towards the tourist satisfaction. With respect to the findings, service provide must carefully review their marketing strategy especially related to the service quality and value. Both are not only interrelated but involved in belief, perception and emotions, that is intangible and subjective. Service provider that are able to position and offer the high benefits over cost will definitely gain more supports from customer or tourist.